Management of ascending aorta perforation during transseptal puncture for left atrial appendage closure: a case report. Issue 4 (30th April 2021) - Schamroth Pravda, Nili; Codner, Pablo; Vaknin Assa, Hana; Hirsch, Rafael
Abstract: Background: An 82-year-old female with a history of atrial fibrillation and repeated episodes of major bleeding on direct oral anticoagulant therapy, with a high risk for thromboembolism and was referred for left atrial appendage closure. Case summary: During the procedure, an unrecognized puncture of the aorta by the transseptal puncture (TSP) needle and inadvertent advancement of the sheath resulted in ascending aorta perforation. This perforation was closed percutaneously using an Amplatzer™ Duct Occluder (ADO). Reversal of heparinization with protamine sulphate was given to avoid intractable bleeding. However, this resulted in thrombus formation and subsequent embolization causing an ST-elevation myocardial infarction. This was treated with balloon dilatation and thrombus aspiration with subsequent Thrombolysis in Myocardial Infarction 3 flow. Discussion: Inadvertent ascending aorta perforation is a rare yet serious complication that can occur during TSP. Percutaneous closure using an ADO is a viable management option. The reversal of heparin carries a risk of thrombus formation and should be avoided in cases where there is no evidence of overt bleeding.